Floating microspheres of cimetidine: Formulation, characterization and in vitro evaluation - Srivastava A.K.; Ridhurkar D.N.; Wadhwa S. (My University, 2025)
The present study involves preparation and evaluation of floating microspheres with cimetidine as model drug for prolongation of gastric residence time. The microspheres were prepared by the solvent evaporation method using polymers hydroxypropylmethyl cellulose and ethyl cellulose. The shape and surface morphology of prepared microspheres were characterized by optical and scanning electron microscopy, respectively. In vitro drug release studies were performed and drug release kinetics was evaluated using the linear regression method. Effects of the stirring rate during preparation, polymer concentration, solvent composition and dissolution medium on the size of microspheres and drug release were also observed. The prepared microspheres exhibited prolonged drug release (∼ 8 h) and remained buoyant for > 10 h. The mean particle size increased and the drug release rate decreased at higher polymer concentration. No significant effect of the stirring rate during preparation on drug release was observed. In vitro studies demonstrated diffusion-controlled drug release from the microspheres.